Online labour index: Measuring the online gig economy for policy and research - Kässi, O; Lehdonvirta, V (Elsevier, 2018)
Labour markets are thought to be in the midst of a dramatic transformation, where standard employment is increasingly supplemented or substituted by temporary work mediated by online platforms. Yet the scale and scope of these changes is hard to assess, because conventional labour market statistics and economic indicators are ill-suited to measuring this “online gig work”. We present the Online Labour Index (OLI), an experimental economic indicator that approximates the conventional labour market statistic of new open vacancies. It measures the utilization of online labour across countries and occupations by tracking the number of projects and tasks posted on major online gig platforms in near-real time. The purpose of this article is to introduce the OLI and describe the methodology behind it. We also demonstrate how it can be used to address previously unanswered questions about the online gig economy. To benefit policymakers, labour market researchers and the general public, our results are published in an interactive online visualisation which is updated daily.